2016
DOI: 10.1519/jsc.0000000000001320
|View full text |Cite
|
Sign up to set email alerts
|

Physical Characteristics Underpinning Lunging and Change of Direction Speed in Fencing

Abstract: Turner, A, Bishop, C, Chavda, S, Edwards, M, Brazier, J, Kilduff, LP. Physical characteristics underpinning lunging and change of direction speed in fencing. J Strength Cond Res 30(8): 2235-2241, 2016-Lunge velocity (LV) and change of direction speed (CODS) are considered fundamental to success during fencing competitions; investigating the physical characteristics that underpin these is the aim of this study. Seventy fencers from the British Fencing National Academy took part and on average (±SD) were 16.83 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 15 publications
4
32
0
2
Order By: Relevance
“…Tsolakis and vagenas (25) showed that lunging time measured by photocells, significantly correlated to body fat and leg power (squat, countermovement jump and reaction strength index, rsI), while with respect to fencing agility testing, body height, countermovement jump and reaction strength index (rsI) provided significant correlations, thus revealing the importance of different training modalities in improving leg muscle strength. Moreover, in another recent study the best predictor of both lunging performance and agility fencing speed was the standing long jump, showing that horizontal jumping drills are also essential to increase fencers' leg power (28).…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Tsolakis and vagenas (25) showed that lunging time measured by photocells, significantly correlated to body fat and leg power (squat, countermovement jump and reaction strength index, rsI), while with respect to fencing agility testing, body height, countermovement jump and reaction strength index (rsI) provided significant correlations, thus revealing the importance of different training modalities in improving leg muscle strength. Moreover, in another recent study the best predictor of both lunging performance and agility fencing speed was the standing long jump, showing that horizontal jumping drills are also essential to increase fencers' leg power (28).…”
Section: Introductionmentioning
confidence: 94%
“…velocity of changing directions was measured using Microgate, Italy photocells with a 4-2-2-4 m shuttle test as described by Turner et al (28). Interclass coefficient of variation ICC was 0.91, (p<0.001).…”
Section: Change Of Direction Velocity (Codv) 4-2-2-4 M Fencing Testmentioning
confidence: 99%
See 3 more Smart Citations